Biological effectiveness of He-3 and He-4 ion beams for cancer hadrontherapy: a study based on the BIANCA biophysical model. (28th September 2021) - Carante, M P; Embriaco, A; Aricò, G; Ferrari, A; Mairani, A; Mein, S; Ramos, R; Sala, P; Ballarini, F
Abstract: While cancer therapy with protons and C-ions is continuously spreading, in the near future patients will be also treated with He-ions which, in comparison to photons, combine the higher precision of protons with the higher relative biological effectiveness (RBE) of C-ions. Similarly to C-ions, also for He-ions the RBE variation along the beam must be known as precisely as possible, especially for active beam delivery systems. In this framework the BIANCA biophysical model, which has already been applied to calculate the RBE along proton and C-ion beams, was extended to 4 He-ions and, following interface with the FLUKA code, was benchmarked against cell survival data on CHO normal cells and Renca tumour cells irradiated at different positions along therapeutic-like 4 He-ion beams at the Heidelberg Ion-beam Therapy centre, where the first He-ion patient will be treated soon. Very good agreement between simulations and data was obtained, showing that BIANCA can now be used to predict RBE following irradiation with all ion types that are currently used, or will be used soon, for hadrontherapy. Thanks to the development of a reference simulation database describing V79 cell survival for ion and photon irradiation, these predictions can be cell-type specific because analogous databases can be produced, in principle, for any cell line. Furthermore, survival data on CHO cells irradiated by a He-3 beam were reproduced to compare the biophysical properties of He-4 and He-3 beams, which is currently an open question. This comparison showed that, at the same depth, He-4 beams tend to have a higher RBE with respect to He-3 beams, and that this difference is also modulated by the considered physical dose, as well as the cell radiosensitivity. However, at least for the considered cases, no significant difference was found for the ratio between the RBE-weighted dose in the SOBP and that in the entrance plateau.